Proposta teórico-interpretativa em sexualidade infantil: contribuição à educação sexual a partir da Grounded Theory - Silva, Claudionor Renato da [UNESP] (2015)
The Grounded Theory (GT) is an inductive research method that is based on the everyday data analysis to generate theory. This thesis is a theoretical and interpretative proposal on child sexuality and its contribution to the area of sex education, a theory which organizes the production of knowledge on the subject. It is a bibliographical and documentary research, as the constructivist aspect of GT Kathy Charmaz. Under the main heading infantile sexuality were accessed and coded articles, monographs, dissertations and indexed theses in Google Scholar, from 2004 to 2014, as well as dissertations and theses in the data loading phase, held at the Bank of CAPES Theses (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior). The encoding that allowed the organization of the fragments of the indexed texts originated in the Sentences categories Coded (SCC). These SCC is the first product resulting from the coding of the fragments of the texts. The SCC generated Categories Units (UC) that are a second product, following the GT method, which coalesce and regroup the SCC in the search for a simplifying contour to theorizing in progress. These UC enabled the systematization of the first concepts of the theory that it is the Provisional Concept Units (UCP), the Memorandum basis for the theory that lead in children's sexuality. This theory is based on three considerations: (1) child sexuality has its reference in Freud and psychoanalysis to the contemporary; (2) the school routine shows two situations that complement each other, creating the need for action both in the field of initial teacher training in pedagogy, and in continuing education in public and private / private education networks; (3) the issue of public policies for protection of children's sexuality as a right of the small child. The first consideration is evident in the privilege of a theoretical approach to the field of psychology explanations that support sexuality in...